Climate stress testing - Hyeyoon Jung; Robert F. Engle; Richard B. Berner (Federal Reserve Bank of New York, 2021)
Climate change could impose systemic risks upon the financial sector, either via disruptions in economic activity resulting from the physical impacts of climate change or changes in policies as the economy transitions to a less carbon-intensive environment. We develop a stress testing procedure to test the resilience of financial institutions to climate-related risks. Specifically, we introduce a measure called CRISK, systemic climate risk, which is the expected capital shortfall of a financial institution in a climate stress scenario. We use the measure to study the climate-related risk exposure of large global banks in the collapse of fossil-fuel prices in 2020.
Keywords: Q54; C53; G20; 330; climate risk; financial stability; stress testing